Tunisia : 2012 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Tunisia. (IMF Staff Country Reports; Country Report ;, 2012)
This 2012 Article IV Consultation highlights that Tunisia experienced a severe recession in 2011 amid domestic and regional turmoil. Real GDP contracted by 1.8 percent, reflecting a sharp decline in tourism and foreign direct inflows. As a result of the economic downturn and the return of Tunisian workers from Libya, unemployment soared to 19 percent in 2011, with youth unemployment at 42 percent. Tunisia's medium-term economic growth potential remains favorable, but unleashing it requires a comprehensive package of structural reforms to foster private investment.